Journeymen's Associations in England in the Late Middle Ages - W. J. A. (Quarterly Journal of Economics, 1897)
Journeymen's Associations in England in the Late Middle Ages Get access W. J. A. W. J. A. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 11, Issue 2, January 1897, Pages 214–215, https://doi.org/10.1093/qje/11.2.214 Published: 01 January 1897